Prevalence and caries-related risk factors in schoolchildren of 12- and 15-year-old: a cross-sectional study - N. Obregón-Rodríguez; P. Fernández-Riveiro; M. Piñeiro-Lamas; E. Smyth-Chamosa; A. Montes-Martínez; M. M. Suárez-Cunqueiro (BMC, 2019)
Abstract Background To assess the prevalence and severity of caries in 12- and 15-year-old schoolchildren, and to analyse the related risk factors. Methods We conducted a cross-sectional study on a random sample of 1843 schoolchildren aged 12 and 15 from Galicia (northwest of Spain). Self-administered questionnaire and dental clinical examination were performed to obtain information about oral health habits, dental caries and oral hygiene. A logistic regression model including dental-caries-related variables was generated for each age group. Results The respective findings for 12- and 15-years-old were as follows: decayed, missing, filled teeth index both for permanent and temporary dentition (DMFT/dmft) of 0.89 (95% CI, 0.87-0.91) and 1.38 (95% CI, 1.33-1.43), respectively; caries prevalence 39.6% (95% CI, 36.3-42.9) and 51.7% (95% CI, 48.0-55.4), respectively. In the 12-year-old group, individuals who occasionally, never or hardly ever brushed their teeth had higher values of caries (OR = 1.83, 95% CI 1.07-3.15, and OR = 9.14, 95% CI1.63-51.17, respectively). Also, the presence of plaque on more than 1/3 gingival was statistically associated with an increase of caries (OR = 2.03; 95% CI, 1.11-3.70), and living in a rural environment was a risk factor (OR = 1.3; 95% CI,1.02-1.80). In the 15-year-old group, higher caries risk was found when brushing was performed once a day (OR = 1.61; 95% CI,1.03-2.50), and among individuals who visited private clinics (OR = 1.77; 95% CI, 1.17-2.66), while electric toothbrush was associated with a lower caries risk (OR = 0.50; 95% CI, 0.29-0.86). Conclusions This study revealed that risk factors of dental caries showed differences in schoolchildren of 12- and 15-year-old. Strongest evidence related to caries in 12-year-old group were found in frequency of toothbrushing and dental plaque. In 15-year old group, electric toothbrush, time since the last visit to the dentist and type of dental care (public/private) had a stronger association with dental caries. Caries prevalence and mean DMFT/dmft increased from 12- to 15-year-old, in spite of improvement in oral hygiene at the age of 15.